LEGAL STATUS OF PERSONALITY AND RESPONSIBILITY OF THE STATE BEFORE THE PERSONALITY AS AN INDICATOR OF THE DEMOCRACY OF THE COMPANY (Journal of actual problems of jurisprudence, 2019)
In this article the author writes the legal status of the person and responsibility of the state to the individual as an indicatordemocratic society